EFEK DOSIS PUPUK KANDANG DAN SUMBER NITROGEN TERHADAP PERTUMBUHAN BIBIT TANAMAN LIDAH BUAYA (Aloe vera L.) DI LAHAN PASIR - Reci Syaputra; Maria Theresia Darini; Darnawi Darnawi (Universitas Sarjanawiyata Tamansiswa, 2018)
The study aims to know the dose of manure and nitrogen source on growth of aloe vera seed in sandy soil. The experiment was conducted in Cangkring vilage, Poncosari, Serandakan, Bantul, D.I Yogyakarta, in 25 meter above sea level and the temperature is 30 ºC - 35 ºC. The research was done in January – May 2017. This reseach arranged in randomized Complete Block Design with 3 repetitions. The first factor is manure dose consisted of 2 levels namely : (K1) 15 ton.ha-1, (K2) 30 ton.ha-1. The second factor is nitrogen source consisted of 4 levels : (N1) urea, (N2) ZA, (N3) NPK dan (N4) KNO3 450 each 450 kg.ha-1. The analysis of data used Analysis of Variance at level of 5%, is continued with Duncan’s Multiple Range Test 5%. The result showed that there was no interaction between dose of cow manure and nitrogen source to all variable except the height of plants. The dose of cow manure did not influence the growth of the aloe vera seedling, like as nitrogen sources